2014
DOI: 10.1021/cm501109r
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Atomic Layer Deposition of Copper Films Using Borane Dimethylamine as the Reducing Co-reagent

Abstract: The atomic layer deposition (ALD) of Cu metal films was carried out by a two-step process with Cu(OCHMeCH 2 NMe 2 ) 2 and BH 3 (NHMe 2 ) on Ru substrates and by a three-step process employing Cu(OCHMeCH 2 NMe 2 ) 2 , formic acid, and BH 3 (NHMe 2 ) on Pd and Pt substrates. The two-step process demonstrated self-limited ALD growth at 150 °C with Cu(OCHMeCH 2 NMe 2 ) 2 and BH 3 (NHMe 2 ) pulse lengths of ≥3.0 and ≥1.0 s, respectively. An ALD window was observed between 130 and 160 °C, with a growth rate of about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 53 publications
4
65
0
Order By: Relevance
“…Cu(dmap) 2 has also been previously used in experiments due to its high decomposition temperatures, low non-volatile residue and high sublimation rate 52 ZnEt 2 is found to dissociate into a ZnEt fragment and Et on a bare copper surface. The…”
Section: Discussionmentioning
confidence: 99%
“…Cu(dmap) 2 has also been previously used in experiments due to its high decomposition temperatures, low non-volatile residue and high sublimation rate 52 ZnEt 2 is found to dissociate into a ZnEt fragment and Et on a bare copper surface. The…”
Section: Discussionmentioning
confidence: 99%
“…It is extremely difficult to deposit continuous thin films of Cu at 2 nm thickness and instead formation of Cu islands with size of 10-90 nm tends to be more favourable. 9 Of these deposition approaches, ALD shows the most promise in surmounting the island growth problem as well as meeting future demands of device scaling. [10][11][12] Many copper organometallic compounds are used with H 2 or H 2 plasma in copper ALD experiments [13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…6 Kalutarage et al compared twostep and three-step processes using the ALD reaction of Cu(dmap) 2 with BH 3 (NHMe 2 ) and separately with BH 3 (NHMe 2 ) and HCO 2 H. 9 They showed that the two-step process requires a Cu seed layer, and affords a growth rate of about 0.13 Å/cycle within the 130−160 °C ALD window.…”
Section: Introductionmentioning
confidence: 99%
“…13 In these cases, the Cu(dmap) 2 precursor is successful because of its relatively high vapor pressure and thermal stability. Given these promising developments, the reaction mechanism and surface chemistry of Cu(dmap) 2 precursor during Cu ALD should be carefully investigated in order to identify better precursors and design new ALD processes for Cu as well as other metals.…”
Section: Introductionmentioning
confidence: 99%